Pipeline right-of-way encroachment in Arepo, Nigeria - Michael Ajide Oyinloye; Isaac Oluwadare Olamiju; Benjamin Lanre Oladosu (Journal of Transport and Land Use)
Encroachment by host communities on pipeline right-of-way (PROW) constitutes a major problem for the oil and gas sector of the economy. This paper uses remote sensing and geographic information system (GIS) technologies to assess the level of vulnerability of people living along the PROW in Arepo, Ogun State, Nigeria. A satellite imagery of the community was acquired and processed using ArcGIS computer software. A GIS buffering operation was performed on the PROW using 15 m, 30 m, 60 m, and 90 m distances, respectively. Three hundred and forty buildings were identified in the buffered zones, out of which 200 (60%) were randomly selected for the study. A structured questionnaire was administered to household heads in the sampled buildings. Empirical analysis shows that 140 buildings (70%) observed less than a 30 m setback to the pipeline. Also, residents benefit from incidents of oil spillage and see these as an avenue to vandalize the pipeline, making them more vulnerable. GIS analysis shows that more than 30% of respondents are highly vulnerable to the hazard of pipeline explosion incidents. Enforcement of setback regulations by the Town Planning Authority and public education and awareness of risks associated with encroachment on the PROW are canvassed among others.